THE INFLUENCE OF SERVICE QUALITY, PRICE PERCEPTIONS AND EXPERIENTIAL MARKETING ON WORLD OF MOUTH IN MANDIRI BINA PRESTASI UNIVERSITY (UMBP) STUDENTS - Christy Ardelia Tarigan; Sugih Arto Pujangkoro; Rulianda Purnomo Wibowo (CV. Radja Publika, 2023)
This study examines the Quality Of Service, Perception Of Price And Experimental Marketing On The World Of Mouth In Students Of Mandiri University Develop Achivements. As for this research method is quantitative, with data collection in the form of a questionnaire. while the respondents were students. The conclusions from this study are first that service quality has a positive and significant effect on Word of Mouth among Mandiri Bina Prestasi University (UMBP) students; Second, 2. That Perceived Price has a positive and significant effect on Word of Mouth for Mandiri Bina Prestasi University Students (UMBP); Third, that Experiential Marketing has a positive and significant influence on Word of Mouth for Mandiri Bina Prestasi University (UMBP) students; Fourth, 4. That Service Quality, Perceived Price and Experiential Marketing simultaneously have a positive and significant effect on Word of Mouth in Mandiri Bina Prestasi University Students (UMBP).